Routine HIV Testing among Hospitalized Patients in Argentina. Is It Time for a Policy Change? - Socías, María Eugenia (Public Library of Science, 2013)
INTRODUCTION: The Argentinean AIDS Program estimates that 110,000 persons are living with HIV/AIDS in Argentina. Of those, approximately 40% are unaware of their status, and 30% are diagnosed in advanced stages of immunosuppression. Though studies show that universal HIV screening is cost-effective in settings with HIV prevalence greater than 0.1%, in Argentina, with the exception of antenatal care, HIV testing is always client-initiated. OBJECTIVE: We performed a pilot study to assess the acceptability of a universal HIV screening program among inpatients of an urban public hospital in Buenos Aires. METHODS: Over a six-month period, all eligible adult patients admitted to the internal medicine ward were offered HIV testing. Demographics, uptake rates, reasons for refusal and new HIV diagnoses were analyzed. RESULTS: Of the 350 admissions during this period, 249 were eligible and subsequently enrolled. The enrolled population was relatively old compared to the general population, was balanced on gender, and did not report traditional high risk factors for HIV infection. Only 88 (39%) reported prior HIV testing. One hundred and ninety (76%) patients accepted HIV testing. In multivariable analysis only younger age (OR 1.02; 95%CI 1.003-1.05) was independently associated with test uptake. Three new HIV diagnoses were made (undiagnosed HIV prevalence: 1.58%); none belonged to a most-at-risk population. CONCLUSIONS: Our findings suggest that universal HIV screening in this setting is acceptable and potentially effective in identifying undiagnosed HIV-infected individuals. If confirmed in a larger study, our findings may inform changes in the Argentinean HIV testing policy.